Investigating Grade 3 learners' changing mathematical proficiency in a maths club programme focused on number sense progression - Hebe, Gasenakeletso Ennie (Rhodes University, Faculty of Education, Department of Education, 2018)
Recent international reports, for example TIMSS (2011 & 2015), point to serious challenges in South African learner performance in Mathematics and Science. Of greatest concern is that research findings (e.g. Graven, Venkat, Westaway and Tshesane 2013) suggest that many South African learners show signs of mathematical knowledge gaps in the lower grades. Hence, there is a need to address challenges of this nature very early in Foundation Phase. This study was undertaken with a view to contribute towards addressing mathematical challenges encountered by learners in Foundation Phase. This empirical enquiry was undertaken under the auspices of the South African Numeracy Chair Project (SANCP) at Rhodes University whose mission is to develop sustainable ways of improving quality teaching and learning of Mathematics in South Africa. A relatively new SANCP programme called Pushing for Progression (PfP) run as part of the after-school Maths Clubs to develop the number sense and four Operations in learners was used to achieve the research aims of this study. Research participants were drawn from the Maths Clubs established by the researcher in a small rural town of Ottosdal in the North West Province of South Africa. This Study is grounded on the Vygotskian perspective and uses the interpretivist qualitative research method for data collection and analysis. Sampling was done opportunistically by enlisting participants (12 teachers and 117 learners) on the basis of their availability and willingness to participate. Pre- and post-assessment of learners' proficiency on the four Basic Operations was conducted at the beginning and at the end of the research project, respectively. This was done to determine the impact of the project on learner performance. Data analysis was done thematically and through the comparison of learner results of the pre- and post-assessment. The findings point to the effectiveness of the PfP Programme in learner performance. This can be deduced from improved scores between pre- and post-assessment and the observations made by participant-teachers on their respective club learners' mathematical proficiencies. Accordingly, based on the findings, this study recommends, inter alia, that since the PfP programme is still in its early stages, similar research be conducted elsewhere. Additionally, the Department of Basic Education could consider exploring the PfP programme as one of several other strategies to help improve learner proficiency in Mathematics.
Keywords: Mathematical ability -- Testing; Education, Elementary -- South Africa; Mathematics -- Study and teaching (Elementary) -- Activity programs; Mathematics -- Remedial teaching; South African Numeracy Chair Project (SANCP)